Health Education on Anemia Among Pregnant Women - Baharika Suci Dwi Aningsih; Ni Nyoman Sri Artina Dewi; Yosefin Beni Purbo Utami (AMK : Abdi Masyarakat UIKA, 2026)
Anemia during pregnancy remains a significant public health problem that increases the risk of maternal and fetal complications. Although the prevalence in Jakarta is lower than the national average, anemia among pregnant women remains common in the Menteng Community Health Center, Central Jakarta. This condition is associated with limited knowledge of balanced nutrition, poor adherence to iron supplementation, and inadequate participation in routine antenatal care. This community service activity aimed to improve pregnant women's knowledge and awareness regarding anemia prevention through health education. The program included a baseline survey to assess participants' knowledge and behavior, interactive health education on balanced nutrition, iron supplementation, and regular antenatal care, followed by a post-education evaluation using a questionnaire. The expected outcomes were improved knowledge and positive behavioral changes in maintaining a healthy diet, regularly consuming iron tablets, and attending routine antenatal care. In conclusion, health education is an effective promotive and preventive strategy to enhance anemia prevention among pregnant women.